Tennis Video 2.0: A new presentation of sports videos with content separation and rendering - Lai, J. H.; Chen, C. L.; Kao, C. C.; Chien, S. Y. (Journal of Visual Communication and Image Representation, 2011)
This paper proposes a new method for presenting sports videos. Tennis videos are used as an example for the implementation of a viewing program called as Tennis Video 2.0. For the methods in video analysis, background generation by considering the pixels in temporal and spatial distribution is proposed; foreground segmentation combining automatic trimap generation and matting model is proposed. To provide more functions in watching videos, the rendering flow of video contents and the semantic Scalability are proposed. With the new analysis and rendering tools, the presentation of sports videos has three properties—Structure, Interactivity, and Scalability. The experiments show that several broadcasting game videos are employed to evaluate the robustness and performance of the proposed system. For user study, 20 evaluators highly identify that Tennis Video 2.0 is a new presentation of sports videos and give people better viewing experience.